Development of Discovery Learning Module on Chemical Equilibrium for Improvement of Critical Thinking Skills: A Case of Senior High School Students in Indonesia - E. Ellizar; S. D. Putri; M. Azhar; H. Hardeli (Research Highlights in Language, Literature and Education Vol. 3, 2023)
The goal of this study is to create a discovery instructional module on chemical equilibrium to help senior high school students improve their critical thinking skills. The discovery learning module with a scientific approach is equipped with teaching materials that contain stimulation, where students are introduced to the problem, led to solving the problem systematically. Teachers act as facilitators and motivators of student learning. This research was based on an observation that was found that the learning instruction was not yet optimal to train students to think critically. This study falls under the category of research and development that employs the Plomp Model, which has three stages: preliminary research, prototyping, and evaluation. The assessment phase was carried out in two schools, with students of high and low academic ability participating. The instrument used was a critical thinking test consisting of nine essay questions. The results showed that generated discovery learning module on chemical equilibrium was effective to improve critical thinking skills, both for students with high and low academic ability.